Assessing preferences for attributes of city information points. Results from a choice experiment. - Grilli, Gianluca; Tomasi, Silvia; Bisello, Adriano (Springer, 2018)
A choice experiment has been carried out to assess the preferred attributes of information points, called totems, to be installed in the city of Bolzano. Totems allow the acquisition, exchange and query of data in real time, as well as provide other services such as electricity or water supply. These infrastructures could be useful for both inhabitants and tourists in need of parking spaces, information about events or charging stations for vehicles. To design them in a cost-effective way, it is important to understand potential users' preferences. For this reason, field surveys using stated preferences are important sources of information to tailor these totem effectively. In order to facilitate the interpretation of results for policy making, estimations are carried out in willingness-to-pay space and by means of a random parameters logit model. Results indicate that the preferred attributes are the presence of Wi-Fi 'hot spots', charging stations for electric cars and bikes and real-time information about available car parks.
Keywords: Innenstadt; Informationssystem; Digitalisierung; Kommunikationsmedium; Tourismus; Parkleitsystem